Interest Rate Risk of Savings Accounts - Jiri Witzany; Martin Divis (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Interest rate risk measurement and management of non-maturity deposit balances presents a challenge for practitioners and academic researchers as well. The paper provides a review of several methodological approaches focusing on the area of savings accounts rate sensitivity modeling and estimation. The proposed models are tested on a Czech banking sector dataset providing mixed results regarding the cointegration type models generally recommended in the literature. On the other hand, the analysis shows that simpler regression models may provide more robust results if the cointegration tests between the saving accounts rate and the market rate series fail.
Keywords: C32; E43; E58; G21; 330; Interest rate risk; savings accounts; non-maturity deposits; cointegration; pass through rate